Fractalkine/CX3CR1 Pathway in Neuropathic Pain: An Update - Silva, Rita; Malcangio, Marzia (Frontiers in Pain Research, 2021)
Injuries to the nervous system can result in a debilitating neuropathic pain state that is often resistant to treatment with available analgesics, which are commonly associated with several side-effects. Growing pre-clinical and clinical evidence over the last two decades indicates that immune cell-mediated mechanisms both in the periphery and in the Central Nervous System (CNS) play significant roles in the establishment and maintenance of neuropathic pain. Specifically, following peripheral nerve injury, microglia, which are CNS resident immune cells, respond to the activity of the first pain synapse in the dorsal horn of spinal cord and also to neuronal activity in higher centres in the brain. This microglial response leads to the production and release of several proinflammatory mediators which contribute to neuronal sensitisation under neuropathic pain states. In this review, we collect evidence demonstrating the critical role played by the Fractalkine/CX3CR1 signalling pathway in neuron-to-microglia communication in neuropathic pain states and explore how strategies that include components of this pathway offer opportunities for innovative targets for neuropathic pain.